The Cambridge companion to Latin love elegy - Thorsen, Thea S. (Cambridge University Press, 2013)
Latin love elegy is one of the most important poetic genres in the Augustan era, also known as the golden age of Roman literature. This volume brings together leading scholars from Australia, Europe and North America to present and explore the Greek and Roman backdrop for Latin love elegy, the individual Latin love elegists (both the canonical and the non-canonical), their poems and influence on writers in later times. The book is designed as an accessible introduction for the general reader interested in Latin love elegy and the history of love and lament in Western literature, as well as a collection of critically stimulating essays for students and scholars of Latin poetry and of the classical tradition.
Title from publisher's bibliographic system (viewed on 09 Nov 2015)
Keywords: Aufsatzsammlung; Latein; Liebeselegie